Training and Assistance in Preparation of Internal Quality Assurance System Documents for Private Universities in Dumai City, Riau Province - Zulkarnain, Zulkarnain; Suryanita, Reni; Meiwanda, Geovani (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Higher Education Quality Assurance is a systemic activity to improve the quality of Higher Education in a planned and sustainable manner. Quality assurance in higher education is carried out through the establishment, implementation, evaluation, control, and improvement of Higher Education Standards known as the PDCA cycle. In order to implement the Higher Education Quality Assurance System in tertiary institutions, this community service activity provides training and assistance to private universities in Dumai City in the preparation of university internal quality assurance system (SPMI) documents. The Directorate General of Learning and Student Affairs, Ministry of Research, Technology, and Higher Education does not set a policy of one SPMI implementation model for all Universities, but provides inspiration on the implementation of essential things in SPMI that are required by laws and regulations. Therefore, universities are expected to develop an appropriate SPMI pattern for the state of the university itself. However, not all universities have the same understanding of the implementation of SPMI in accordance with the law. One of them was experienced by partners in this community service activity, namely 7 private universities in Dumai City. The Riau University PKM team participated in helping partner universities to assist in the preparation of SPMI documents based on the condition of partner universities through the Riau University Postgraduate PKM funds. The activity preparation period to activity reporting is 8 weeks. The target of the activity that has been produced is the preparation of the SPMI document at one of the partner universities.